Strategic Implementation of Academic Supervision by School Principals: A SWOT-Based Analysis of Teacher Professional Development - Af'idah, Azimatul; Hariyati, Nunuk; Haq, Mohammad Syahidul; Khamidi, Amrozi (Papanda Publisher, 2025)
Academic supervision by school principals constitutes a critical mechanism for enhancing teacher professionalism and instructional quality, yet implementation challenges persist globally. This qualitative study employed systematic literature review integrated with field observations at two purposively selected elementary schools in Gresik Regency, Indonesia—UPT SD Negeri 15 and UPT SD Negeri 23—both led by principals with